1989
DOI: 10.1007/bf01537281
|View full text |Cite
|
Sign up to set email alerts
|

Amoxycillin/clavulanic acid (augmentin)-induced intrahepatic cholestasis

Abstract: A 75-year-old man developed a biopsy-proven, drug-induced intrahepatic cholestasis after use of amoxycillin trihydrate combined with the beta-lactam inhibitor potassium clavulanate (Augmentin). Cholestatic liver injury is an uncommonly recognized, probably immunologically based adverse reaction to therapy with penicillin and its derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…In all patients, IgM antibodies to hepatitis A virus and hepatitis B surface antigen were absent in serum. Serological tests for hepatitis C virus infection were negative in the six patients tested (patients 1,2,5,7,8,11). Serological tests for recent infection with cytomegalovirus in nine cases (patients [1][2][3][4][5][6][7][8]11), herpes simplex viruses in three patients (patients 1,2,8), and Epstein-Barr virus in six patients (patients 1,2,5,7,8,11) were also negative in all patients tested.…”
Section: Methodsmentioning
confidence: 98%
“…In all patients, IgM antibodies to hepatitis A virus and hepatitis B surface antigen were absent in serum. Serological tests for hepatitis C virus infection were negative in the six patients tested (patients 1,2,5,7,8,11). Serological tests for recent infection with cytomegalovirus in nine cases (patients [1][2][3][4][5][6][7][8]11), herpes simplex viruses in three patients (patients 1,2,8), and Epstein-Barr virus in six patients (patients 1,2,5,7,8,11) were also negative in all patients tested.…”
Section: Methodsmentioning
confidence: 98%
“…Hepatic damage associated with amoxicillin-clavulanate (a semi-synthetic penicillin inhibitor of betalactamase) administered via the oral or parenteral route has been widely recorded since the first case published in 1989 [57][58][59]. Amoxicillin-clavulanate is one of the most frequently prescribed antibiotics worldwide.…”
Section: Hepatotoxicity Related To Main Antibiotic Groups A) Penicillinsmentioning
confidence: 99%
“…Amoxicillin–clavulanic acid (amox‐clav) was first marketed in 1981 and it has become one of the most commonly prescribed antibiotics. Drug‐induced liver injury (DILI) from amox‐clav was reported as early as 1988 and multiple individual cases and several case series have been published since then . Subsequently, large prospective studies have identified amox‐clav as one of the most common agents associated with severe DILI.…”
Section: Introductionmentioning
confidence: 99%